An Automated Pipeline for the Analysis of PET Data on the Cortical Surface - Marcoux, Arnaud; Burgos, Ninon; Bertrand, Anne; Teichmann, Marc; Routier, Alexandre; Wen, Junhao; Samper-González, Jorge; Bottani, Simona; Durrleman, Stanley; Habert, Marie-Odile; Colliot, Olivier; , for the Alzheimer's Disease Neuroimaging Initiative (Frontiers in Neuroinformatics, 2018)
We present a fully automatic pipeline for the analysis of PET data on the cortical surface. Our pipeline combines tools from FreeSurfer and PETPVC, and consists of i) co-registration of PET and T1-w MRI (T1) images, ii) intensity normalization, iii) partial volume correction, iv) robust projection of the PET signal onto the subject’s cortical surface, v) spatial normalization to a template, and vi) atlas statistics. We evaluated the performance of the proposed workflow by performing group comparisons and showed that the approach was able to identify the areas of hypometabolism characteristic of different dementia syndromes: Alzheimer’s disease (AD) and both the semantic and logopenic variants of primary progressive aphasia. We also showed that these results were comparable to those obtained with a standard volume-based approach. We then performed individual classifications and showed that vertices can be used as features to differentiate cognitively normal and AD subjects. This pipeline is integrated into Clinica, an open-source software platform for neuroscience studies available at www.clinica.run.